Arkadia Heleny Radziwłłowej – zagadnienie śmierci w XVIII-wiecznym ogrodzie - Ludwisiak, Małgorzata (Acta Universitatis Lodziensis. Folia Historica, 2003)
The author of the article tried to subject Arcadia near Nieborów, the garden of Helena Radziwiłł (1753-1821) to the formal and textual analysis, paying special attention to the subject of death present there. The garden with its architectural buildings was created in the last quarter of 18th century, inspired by the ideas of English gardens, it was also strongly influenced firstly by the sentimental and secondly by the romantic aesthetics. As early as the first designs were Prepared, the mason ideas were taken into consideration as well. Diffused elements of death symbols existed since the beginning in the whole garden (like e. g. the name of a river – Leta, a mythological river of Forgetting, flowing through Hades). On the Poplar Island there was a tomb errected, modeled after the tomb of J. J. Rousseau, With two inscriptions: Et in Arcadia ego and J’ai fa it Arcadie j'y repose. The intention of the Princess was also do construct in the garden her own real tomb. All these elements of the Karden’s scenery, inspired by the literary sources (arcadian literature and writings of Rousseau the key to understanding the park of Radziwiłł with its widely conceived naturality, idyllical state of happiness and the death theme), formed a part of ideological program of Arcadia and constituted a part of a certain intellectual game. But, since all three daughters of the Princess died one after another (in 1796, 1806 and 1808), death appeared in the garden as a tragic fact. Helena Radziwiłł decided to bury their bodies in the tomb, which she previously Provided for herself. The first such mausoleum in Poland was decorated with carefully elaborated consolation program that had practically nothing in common with Christian eschatology. Death symbols and the burial in the garden are not any novelty introduced by the princess: the death was gradually penetrating European and especially English gardens over 18th century. Nevertheless, on the Polish ground it was quite a new and untypical phenomenon. Moreover, the name of the park – Arcadia – refers in a particular way the garden to the sphere of myth. The decision of burying her daughters in an unholy ground, especially taken in deeply traditional Poland, must have been based on some very strong justification. Among many kinds of sacrum present within the garden symbols, there was surely no place for the Christian sacrum. The space of the garden was rather sanctified by the resurrected mythology, mason esotericism, by the history and time frozen in the collected objects and also by the nature itself. It existed in the park of Helena Radziwiłł in an intensified form, representing, to some extent, the purity and the beauty of the whole nature within only a little fragment of space. Looking for the roots of so deep a transformation of the elite’s mentality of the Enlightenment, we arrive at the Cartesian dualism and its influence on the philosophy and the intellectual atmosphere of the 18th century. In the mechanistic world there was no place left for God Revealed nor his religion. The first goddess of 18th century - the Nature - had sufficient influence on minds and feelings of her worshippers to convince them that she was the first and unquestionable condition of living and sanctifying death. The program and actual breaking with Christian eschatology gave rise to the necessity of some new canon of comprehending death. In this way, the elegiac memories of the buried man - “the contemplative penetrating the idea of mortality” - took the place of the consolation, previously brought by the thoughts of Heaven, Salvation and Resurrection. Arcadia near Nieborów found itself at the end of a long way, which the topos of “a garden as paradise” had to go through, since the times of the Garden of Eden. On the one hand it was still an attempt to create a space for human happiness beyond time where the eternal youth and spring prevailed. On the other hand, along other European gardens of its time, Arcadia constructed a form of a bridge, opening the way to the 19th century gardens of death.